Constituting ethical academics in teacher education: Navigating multiple and conflicting discourses. (January 2022) - Barrow, Mark; Xu, Linlin
Abstract: Many studies on academic identity draw upon a narrow epistemological and empirical base. To broaden this and enrich our understanding, this study explores how university-based teacher educators make sense of and construct their academic identities. We apply Foucault's technologies of the self as a framework to analyse data from teacher education academics working in an education faculty created by the merger of a standalone college of education and a university department. Participants describe a dynamic, tension-filled and on-going process of self-constitution, as they resist and/or comply with multiple, conflicting discourses to knowingly and deliberately transform themselves into ethical academic subjects. Highlights: Teacher educators in research-intensive universities apply various technologies of the self. By applying these technologies, they constitute and transform themselves into ethical academic subjects. This process of self-constitution is dynamic, tension-filled and on-going. The self-constitution involves varying degrees of resistance to, and/or compliance with multiple, conflicting discourses.